Memoryscapes of liberation: activist mnemonic labour in the queer press. - Salerno, Daniele (Cultural Studies, 2025)
In this article, I will explore the role of memory in the context of homosexual liberation movements. I will do this through the lens of the queer press, which will serve as a doorway for the exploration of activist mnemonic labour. Activists undertake mnemonic labour to craft narratives that weave together historical oppression and resistance with hopes for a better future. These narratives are used to motivate and sustain activists in their present struggles. The queer press helps spread narratives across borders and creates shared memoryscapes for activism. My proposal is to view memoryscapes as schemata that inform activist mnemonic labour. On one hand, memoryscapes offer a shared purpose and direction for activists spread across different countries. On the other hand, they serve as arenas for mediation and comparison, linking distinct histories from diverse social groups and revealing their shared threads. This turns memory into a resource for building alliances across borders, and among different political and social groups. I will adopt this perspective to study two Argentinian homosexual liberation groups from the 1960s-70s: Nuestro Mundo and Frente de Liberación Homosexual (FLH). I will explore activist mnemonic labour on Nuestro Mundo's bulletins and the FLH's periodicals: Homosexuales and Somos. I will focus on two main aspects: (1) how activists adapt transnational narratives to the local context, and (2) how Argentinian activists weave narratives that blend historical oppression and resistance with visions of a different future.